PIERCING THE VEIL OF VILLAGE FINANCIAL ACCOUNTABILITY IN INDONESIA: A LEGAL LIABILITY PERSPECTIVE - Henry D. P. Sinaga (Journal of Village and Local Community, 2022)
Transfer income in the Village Revenue and Expenditure Budget (APBDes) is in the context of increasing welfare in rural areas, reducing the gap between cities and villages, and reducing the poverty rate of rural communities in Indonesia. However, in practice, there is still misuse of village finances by certain elements as during 2015-2020 there were 676 defendants in corruption cases committed by village officials. Based on a qualitative approach using secondary data, it is concluded that handling and prevention of village financial abuse in Indonesia is carried out through regulation and enforcement of collective liability, considering that the management of village finances and APBDesa is the result of hard work with all the stakeholders in the village. It is suggested that there will be a renewal of village law which regulates collective liability, both administratively, civilly and criminally.